The effectiveness of gamification technique for higher education students engagement in polytechnic Muadzam Shah Pahang, Malaysia - Ab. Rahman, Rafidah; Ahmad, Sabrina; Hashim, Ummi Rabaah (International Journal of Educational Technology in Higher Education, 2018)
In recent years, gamification is becoming popular in education development to enrich students experience in classroom. However, there is still lack of awareness among educators and the concern of whether the gamification technique is acceptable by students. This paper presents the effectiveness of gamification technique to improve students’ engagement in Database Design subject at Polytechnic Muadzam Shah Pahang, Malaysia. A framework to implement the gamification technique in higher education is also described. As for the evaluation, an empirical investigation method is adapted and data was collected based on Technology Acceptance Model (TAM) and Student Course Engagement Questionnaire (SCEQ). The evaluation results indicate that the students positively inclined towards gamification caused by the ease of the platform used rather than the benefits that they can obtain from the gamification, concluding that Perceived Ease of Use (PEOU) is a better indicator for students’ attitude towards gamification.